2020
DOI: 10.1002/kin.21343
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of photostabilization of cyanocobalamin in liposomal preparations

Abstract: Cyanocobalamin (B 12 ) is a photosensitive vitamin, and its photodegradation to hydroxocobalamin (B 12b ) in liposomes has been investigated. The values of apparent first-order rate constants (k obs ) for the photodegradation of B 12 in liposomes (nine preparations) are in the range of (0.52-2.24) × 10 -3 min -1 , compared to 3.21 × 10 -3 min -1 for B 12 in aqueous solution (pH 5.0). The entrapment efficiency of B 12 in liposomes is 26.4-38.8%. The values of k obs show a linear relation with phosphatidylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
(155 reference statements)
0
7
0
Order By: Relevance
“…This happens because the entrapment is more efficient if the compound is retained in the phospholipid bilayers, which depends on its primary affinity [ 48 , 81 ]. Arsalan et al reported a maximum entrapment efficacy of 40% in B12 liposomes when maximizing the amount of lipid included during the vesicle formulation [ 40 ]. This result is clearly superior to our L1 data ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This happens because the entrapment is more efficient if the compound is retained in the phospholipid bilayers, which depends on its primary affinity [ 48 , 81 ]. Arsalan et al reported a maximum entrapment efficacy of 40% in B12 liposomes when maximizing the amount of lipid included during the vesicle formulation [ 40 ]. This result is clearly superior to our L1 data ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…Biomedical research has led to the development of modified lipid vesicles that include surfactants (transfersomes) or ethanol (ethosomes) in their composition, which provide greater flexibility, causing different carrier–skin interactions and thus enhancing skin drug delivery [ 38 , 39 ]. Cyanocobalamin liposomes have already been prepared by Arsalan et al to improve its photostability and by Vitetta et al to achieve systemic absorption after oral administration [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous reports, ,, we proposed mechanistic details for the formation of C–N and C–O bonds. According to the articles reported in recent years, cyanocobalamin as a vitamin B 12 is converted to hydroxycobalamin in the presence of heat, water, and oxygen. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…According to the articles reported in recent years, cyanocobalamin as a vitamin B 12 is converted to hydroxycobalamin in the presence of heat, water, and oxygen. 20,68,72,73 The central cobalt cation in vitamin B 12 forms has an oxidation state of +3. Co(II) and hydroxyl radical are generated as a result of the homolytic cleavage of hydroxycobalamin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Unfortunately, the conditions used did not allow for the observation of the stabilizing effect of B 12 nanoencapsulation, while the stabilization effect of nanoencapsulation was observed for vitamin C. Maiorova et al emphasized the applicability of nanosystems as carriers for CNCbl by the development and evaluation of nanoengineered polymer capsules and lyotropic liquid-crystalline nanosystems [258]. The incorporation of vitamin B 12 into liposomes has also been shown as an effective approach for its protection from the effect of destabilizing factors [259][260][261]. Liposomes are closed spherical vesicles with a unique structure, composed of a phospholipid bilayer, enabling vitamin B 12 incorporation inside the center aqueous phase, which protects it from degradation.…”
Section: Strategies For Vitamin B 12 Stabilizationmentioning
confidence: 99%